Advances in physical organic chemistry. - Richard, J. P. (John P.) (Elsevier Academic Press, 2005)
Advances in Physical Organic Chemistry provides the chemical community with authoritative and critical assessments of the many aspects of physical organic chemistry. The field is a rapidly developing one, with results and methodologies finding application from biology to solid state physics.